Cadaveric Biomechanical Evaluation of Capsular Constraint and Microinstability After Hip Capsulotomy and Repair. Issue 10 (22nd October 2022) - Donnelly, Emma; Vakili, Samira; Getgood, Alan; Willing, Ryan; Degen, Ryan M.
Background: It remains unclear if capsular management contributes to iatrogenic instability (microinstability) after hip arthroscopy. Purpose: To evaluate changes in torque, stiffness, and femoral head displacement after capsulotomy and repair in a cadaveric model. Study Design: Controlled laboratory study. Methods: A biomechanical analysis was performed using 10 cadaveric hip specimens. Each specimen was tested under the following conditions: (1) intact, (2) portals, (3) interportal capsulotomy (IPC), (4) IPC repair, (5) T-capsulotomy (T-cap), (6) partial T-cap repair, and (7) T-cap repair. Each capsular state was tested in neutral (0°) and then 30°, 60°, and 90° of flexion, with forces applied to achieve the displacement-controlled baseline limit of external rotation (ER), internal rotation (IR), abduction, and adduction. The resultant end-range torques and displacement were recorded. Results: For ER, capsulotomies significantly reduced torque and stiffness at 0°, 30°, and 60° and reduced stiffness at 90°; capsular repairs failed to restore torque and stiffness at 0°; and IPC repair failed to restore stiffness at 30° ( P < .05 for all). For IR, capsulotomies significantly reduced torque and stiffness at 0°, 30°, and 60° and reduced stiffness at 90°; and capsular repairs failed to restore torque or stiffness at 0°, 30°, and 60° and failed to restore stiffness at 90° ( P < .05 for all). For abduction, IPC significantly decreased torque at 60° and 90° and decreased stiffness at all positions; T-cap reduced torque and stiffness at all positions; IPC repair failed to restore stiffness at 0° and 90°; and T-cap repair failed at 0°, 60°, and 90° ( P < .05 for all). For adduction, IPC significantly reduced torque at 0° and reduced stiffness at 0° and 30°; T-cap reduced torque at 0° and 90° and reduced stiffness at all positions; IPC repair failed to restore stiffness at 0° and 90°; and T-cap repair failed at 0°, 60°, and 90° ( P < .05 for all). There were no statistically significant femoral head translations observed in any testing configurations. Conclusion: Complete capsular repair did not always restore intact kinematics, most notably at 0° and 30°. Despite this, there were no significant joint translations to corroborate concerns of microinstability. Clinical Relevance: Caution should be employed when applying rotational torques in lower levels of flexion (0° and 30°).